AuToGraFS: Automatic topological generator for framework structures - Addicoat, Matthew A.; Coupry, Damien E.; Heine, Thomas (Journal of Physical Chemistry A, 2014)
Metal-organic frameworks (MOFs) and covalent organic frameworks (COFs) are recently notable examples of highly porous polymer frameworks with a raft of potential applications. Synthesis of these compounds is modular, with âœconnectorsâ and âœlinkersâ able to be replaced almost at will in the fabrication of isoreticular frameworks (frameworks with the same underlying topology). The range of components available to form such framework structures is vast, leading to a âœcombinatorial explosionâ problem in predicting which framework compounds might have a set of desired properties. Computational investigations can be used in both predictive and explanatory roles in this research but rely on accurate structural models. In this work, we present our software, AuToGraFS, Automated Topological Generator for Framework Structures, and show some of its advanced functionality in âœcomputational reticular chemistryâ. AuToGraFS is linked to a fully featured force field to produce fully optimized structures of arbitrary frameworks. AuToGraFS, including a graphical user interface, is publicly available for download.
CRIS-Team Scopus Importer:2023-03-20